Brand names between the rule of orthography and rule of law - Dobrovoljc, Helena (Linguistica (Ljubljana), 2013)
The article presents the divergence between legal norms and rules of orthography with regard to respect for industrial property. In line with international guidelines, the Slovene Industrial Property Act (ZIL-1) endows the owner of industrial property or a brand name with the exclusive right to its use, thus enabling the owner to prohibit its inappropriate use or demand its unmodified use. On the other hand, industrial product names are also linguistic entities, facts submitted to the rules of language use, changeand transformation. Frequently used names begin to be used in forms that differ from the original forms, a phenomenon that is related to the natural modification of the identification function of the original name. If such forms acquire a generic character their syntactic position is changed (they no longer appear as attributives), the initial letteris no longer capitalised (Kalodont > kalodont), and often the forms are phonetically adapted to the borrowing language (Cognac > konjak). As sources of information about the state of language use, language reference works present the names in these newforms. In light of the fact that brand name owners view generic use as illegal, such owners are legally bound to dispute the otherwise authentic representation of language data in language resources. Lexicographers all over the world are faced with lawyers telling lexicographers which form is allowed to be included in the dictionary (Landau 2001:405407). In Slovenia, we are currently dealing with a legal-orthographic dilemma regarding the use of the names Teflon, Aspirin and Cognac.
Keywords: blagovne znamke; brand names; industrial property (international law); industrijska lastnina (mednarodno pravo); industrijski izdelki; jezikovna raba; language usage; manufactures; marques de commerce; orthographe; orthography; pravopis; propriété industrielle; Slovene; Slovenian language; slovenščina; usage de la langue